Active Gap Filling and Island Constraint in Processing the Mandarin “Gap-Type” Topic Structure - Dong, Zhiyin; Rhodes, Ryan; Hestvik, Arild (Frontiers in Communication, 2021)
There is a long-standing debate concerning whether Mandarin topic constructions are movement-derived and form a filler-gap dependency like the English-type topicalization. This ERP study explores this issue by testing whether island constraints, a diagnostic for movement, are actively observed during online processing of the Mandarin “gap-type” topic construction, an understudied area in Mandarin sentence processing research. Following the paradigm of Traxler and Pickering (1996), we manipulated islandhood (relative clause island conditions vs. no island conditions) and plausibility, or whether the topic is a plausible object of the potential subcategorizing verb based on animacy fit (i.e., “greet a teacher’ vs. “greet a file”) in a 2×2 design. We predict that any plausibility effect obtained for the non-island conditions would disappear for the island conditions if the parser observes the island constraint and avoids positing gaps inside an island. we observed a P600-previously found for animacy violations-for the non-island conditions but not for the island conditions. Additionally, we found a positive-going component occurring from 588ms-792ms at the fronto-central site for the island condition at the potential gap site. While this novel ERP’s interpretation is yet to be determined, it is unlikely to indicate any plausibility effect. Our findings suggest that the parser is sensitive to island constraints in online processing of the Mandarin "Gap-type" topic structure, and lend support to the movement analysis for Mandarin topicalization.